Respeto y promoción de la iniciativa de las comunidades carismáticas - Navarro, Luis (Ius canonicum, 2024)
Ecclesial movements and new communities in the Church stem from charisms. Dealing with them calls for profound respect for their charism, and the appropriate framing of these new realities within the Church. Canonical norms relating to associations of the faithful have been the most common instrument for such framing. Following a presentation of developments in doctrine and legislation, this paper addresses trends in the application of such regulations. The functions of authority have been expanded through both praxis and the new norms now applicable to some associations, leading to a corresponding reduction in the autonomy enjoyed by charismatic initiatives. Finally, some limitations of the current regulations that do not fully respond to the charismatic needs of these new realities are discussed, concluding with a number of proposals intended to overcome them.